Identification of evolutionarily conserved Momordica charantia microRNAs using computational approach and its utility in phylogeny analysis. (October 2015) - Thirugnanasambantham, Krishnaraj; Saravanan, Subramanian; Karikalan, Kulandaivelu; Bharanidharan, Rajaraman; Lalitha, Perumal; Ilango, S.; HairulIslam, Villianur Ibrahim
Graphical abstract: Highlights: Twenty four pre-miRNAs were reported from Momordica charantia developing seed transcriptome. Phylogeny analysis with binary data were unreliable. Identified miRNAs held sequence conservation in mature miRNAs. Phylogeny analysis of pre-miRNA sequences revealed genus specific segregation. Predicted targets revealed role of miRNAs in regulation of developmental process. Abstract: Momordica charantia (bitter gourd, bitter melon) is a monoecious Cucurbitaceae with anti-oxidant, anti-microbial, anti-viral and anti-diabetic potential. Molecular studies on this economically valuable plant are very essential to understand its phylogeny and evolution. MicroRNAs (miRNAs) are conserved, small, non-coding RNA with ability to regulate gene expression by bind the 3′ UTR region of target mRNA and are evolved at different rates in different plant species. In this study we have utilized homology based computational approach and identified 27 mature miRNAs for the first time from this bio-medically important plant. The phylogenetic tree developed from binary data derived from the data on presence/absence of the identified miRNAs were noticed to be uncertain and biased. Most of the identified miRNAs were highly conserved among the plant species and sequence based phylogeny analysis of miRNAs resolved the above difficulties in phylogeny approach using miRNA. Predicted gene targets of the identified miRNAs revealed their importance in regulation of plant developmental process. Reported miRNAs held sequence conservation in mature miRNAs and the detailed phylogeny analysis of pre-miRNA sequences revealed genus specific segregation of clusters.